Ficção curta de autoria feminina paraibana: análise da casa, do corpo e do patriarcado em quatro luas - Silveira, Ana Patrícia Frederico (2020)
This thesis, entitled Short fiction of female authorship from Paraíba: the body, the house and the patriarchy in Quatro Luas, focuses on cultural and gender studies, more specifically on gender study, which deals with the female character and how she deals with her body and the spaces that confront her or not with the patriarchal order. It is important to understand that when referring to the female character we are not only reduced to fictional characters, but also to real women who have established themselves in society as literary works authors, produced in the Paraíba’s territory, since the 19th century. This research, therefore, understands feminist criticism as our main aspect, so it is aimed at rescuing women who made literature one of their activities, as a way to show and share their awareness of themselves on the path they take that emancipates her as a citizen, without allowing her voice to be extinguished, in the name of the order prevailed interest of by the men who insist on the women’s memoricide. We highlight the relevance of carrying out this study without disentangling the female voice and her body, inserted in the literary fiction spaces, considering that voice and body were and still are weapons of great power of dominance and power in the field of existence and women’s perpetuation. For this, we reserve the study of the work Quatro Luas, produced at the beginning of the 21st century, as a way of investigating how the authors who make up this work, revealed themselves at the turn of the century, dialoguing our discoveries as literary critics with the consecrated studies on this area, the character and the body, in the scenario of Brazilian female authorship, following the same methodology used by Elódia Xavier, when she investigated the body and the house in the Brazilian female authorship, our cut being exclusively focused on Quatro Luas. Many other research resources guided us and explains what it means to be a woman, what it means to be from Paraíba and the various nuances of feminism, as symbols of resistance and struggle in the scene of women's emancipation, freedom and power.